THE USE OF MIND MAPPING STRATEGY TO IMPROVE THE ABILITY OF THE SECOND YEAR STUDENTS OF MA MUHAMMADIYAH PEKANBARU IN WRITING ANALYTICAL EXPOSITION TEXT - Rita Dwi Indah Wulandari; Hadriana '; Erni ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This classroom action research aimed to find out whether mind- mapping strategy can improve students’ writing ability in analytical exposition text and to find out to what extend mind mapping improve students’ writing ability in analytical exposition text. This research was conducted at MA Muhammadiyah Pekanbaru from March to October 2015. The number of participant was 31 students of XI social class. This research consisted of two cycles. The instruments of this research were writing test, observation sheet, and field note. The finding showed that the average score of pre- test was 56.88. It improved to 70.18 in the first post test and 78.75 in the second post test. Based on the improvement, it can be concluded that mind mapping strategy can improve the ability of the second year students of MA Muhammadiyah Pekanbaru in writing analytical exposition text. In addition, mind mapping strategy also improves students’ writing ability in all aspects of writing.Keywords: action research, writing ability, mind mapping, analytical exposition texts